Proceedings of the 2nd International Symposium on Partial Least Squares Path Modeling: The Conference for PLS Users 2015
DOI: 10.3990/2.327
|View full text |Cite
|
Sign up to set email alerts
|

Interaction and brand experience as a path for brand love: a PLS-SEM marketing application

Abstract: Interaction through online social networking sites is one of the most relevant topics nowadays. In the other hand, brand experience has become a powerful for marketers also creating an important bond. Considering both constructs, we propose to analyze the effect of them as a path of the brand love. We analyze the effect of interaction and brand experience on brand love. We conducted a path analysis using PLS-SEM. This paper explores a new way for marketers to improve the engagement with consumers. These intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Vyas and van der Veer (2005) pointed out that the core of user experience with information systems is the quality of interaction. Barajas Portas (2015) found that the interaction between consumers and brands has a positive impact on brand experience. Costello (2018) also confirmed that high-quality game interaction can enhance the player ’s computer game experience.…”
Section: Theoretical Framework Research Hypotheses and Model Establis...mentioning
confidence: 99%
“…Vyas and van der Veer (2005) pointed out that the core of user experience with information systems is the quality of interaction. Barajas Portas (2015) found that the interaction between consumers and brands has a positive impact on brand experience. Costello (2018) also confirmed that high-quality game interaction can enhance the player ’s computer game experience.…”
Section: Theoretical Framework Research Hypotheses and Model Establis...mentioning
confidence: 99%